Life Experiences of Construction Sector Workers in the COVID Context in Lalitpur, Nepal - Adhikari, Devendra (Journal of Training and Development, 2021)
The COVID-pandemic has hit hard on Nepali's economy and the lives of construction- sector workers. The purpose of this research is to explore the life experiences of construction-sector workers during and post COVID-pandemic. This research adopts a qualitative approach under the socio-constructionism paradigm. Data gathered from in-depth interviews with three participants in the sectors of masonry, house-painting, and plumbing have been used for making out the meaning of the research. The findings of this research reveal that the COVID-pandemic has brought new resilient strategies in the lives of the construction workers such as keeping high concern on personal safety, family’s well-being and exploring employment opportunities through informal networks. Living with the COVID has become possible due to the resiliency and social capital of the workers. This research is helpful to TVET practitioners and academicians to understand the survival strategies of the construction sector workers and plan TVET programs accordingly.